Gender, Age, and Educational Level Attribute to Blood Alcohol Concentration in Hospitalized Intoxicated Adolescents; A Cohort Study. (26th February 2013) - Van, Eva; Van der, Tjeerd; Van, Joris J.; Van der, Nicolaas
<x xml:space="preserve">Abstract</x> Background The prevalence of adolescents hospitalized with acute alcohol intoxication, mainly because of severe reduced consciousness, is increasing. However, the characteristics of these adolescents are mainly unidentified. In this clinical research, we aimed to identify factors that attribute to higher ethanol concentration, on which targeted alcohol health interventions can be designed. Methods Since 2007, alcohol intoxication among adolescents has been one of the leading topics of the Dutch Pediatric Surveillance System. In the current study, we have analyzed which demographic characteristics, general alcohol use behaviors, and clinical intoxication data were related to the blood alcohol concentration (BAC) levels at hospital admittance. We included all adolescents aged <18 years, admitted with BAC >0.0 g/l, and reduced consciousness during the years 2007, 2008, 2009, and 2010. Results A total of 2, 023 adolescents with alcohol intoxication were reported, and 1, 618 questionnaires were returned, of which 1, 350 met our inclusion criteria. In univariate analysis, age, gender, educational level, place of alcohol purchase, place of alcohol consumption, age of first drink, and regular alcohol use during the weekend correlated with higher BAC. After multivariate analysis, older adolescents, boys, and higher educational level significantly attributed to higher BAC at admittance. Conclusions In alcohol‐intoxicated adolescents with reduced consciousness, gender, age, and also educational level correlate with BAC at admittance. Explanatory factors could be found in sensitivity to alcohol, but also in socioeconomic factors, which influence availability. Intervention strategies could be targeted more specific now for the subgroups found in this study to decrease the growing burden of adolescent alcohol intoxication, both on the societal level and on the clinical level.